Evaluación de la aceptación del seguro agrícola en la zona norte de los Ríos año 2012. - Tarira Zamora, Jorge Luis (2013)
This research was carried oct between the months of October, 2012 to February, 2013, has made in order to evaluate the acceptance of the Agricultural Insurance in the north area of the province Los Rios, means poll carried out to farmers who hare this type of insurance we were ah it was to clear several doubts with regard to this topic, in addition know the situation of the farmers the respect to the bidder of the service. Company implemented The National Government for years the agricultural credits which are delivered by means of the Banco Nacional de Fomento but this is not stay there in order that the farmers could obtain an agricultural credit they will have to contract an agricultural insurance policy, to which the government subsidizes 60 % of the cost of this contract. And the farmers cancel the difference most of the tax laur. We found that the majority of respondents hold this insurance as a requirement for a loan It we were to stadlish that the majority of the respondents ones support this insurance as a requirement for a lending, more not for taking care of his forming, in the main they support forming of corn in other words in this zone of study the short cycle prevails being so these forming are exposed to several hurts since we cannot provide hurts that can happen for effects of the nature,